If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + 5(x + -3) + -1(-3 + x)(2x + 5) = 0 Reorder the terms: 2 + 5(-3 + x) + -1(-3 + x)(2x + 5) = 0 2 + (-3 * 5 + x * 5) + -1(-3 + x)(2x + 5) = 0 2 + (-15 + 5x) + -1(-3 + x)(2x + 5) = 0 Reorder the terms: 2 + -15 + 5x + -1(-3 + x)(5 + 2x) = 0 Multiply (-3 + x) * (5 + 2x) 2 + -15 + 5x + -1(-3(5 + 2x) + x(5 + 2x)) = 0 2 + -15 + 5x + -1((5 * -3 + 2x * -3) + x(5 + 2x)) = 0 2 + -15 + 5x + -1((-15 + -6x) + x(5 + 2x)) = 0 2 + -15 + 5x + -1(-15 + -6x + (5 * x + 2x * x)) = 0 2 + -15 + 5x + -1(-15 + -6x + (5x + 2x2)) = 0 Combine like terms: -6x + 5x = -1x 2 + -15 + 5x + -1(-15 + -1x + 2x2) = 0 2 + -15 + 5x + (-15 * -1 + -1x * -1 + 2x2 * -1) = 0 2 + -15 + 5x + (15 + 1x + -2x2) = 0 Reorder the terms: 2 + -15 + 15 + 5x + 1x + -2x2 = 0 Combine like terms: 2 + -15 = -13 -13 + 15 + 5x + 1x + -2x2 = 0 Combine like terms: -13 + 15 = 2 2 + 5x + 1x + -2x2 = 0 Combine like terms: 5x + 1x = 6x 2 + 6x + -2x2 = 0 Solving 2 + 6x + -2x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2'. 2(1 + 3x + -1x2) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(1 + 3x + -1x2)' equal to zero and attempt to solve: Simplifying 1 + 3x + -1x2 = 0 Solving 1 + 3x + -1x2 = 0 Begin completing the square. Divide all terms by -1 the coefficient of the squared term: Divide each side by '-1'. -1 + -3x + x2 = 0 Move the constant term to the right: Add '1' to each side of the equation. -1 + -3x + 1 + x2 = 0 + 1 Reorder the terms: -1 + 1 + -3x + x2 = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -3x + x2 = 0 + 1 -3x + x2 = 0 + 1 Combine like terms: 0 + 1 = 1 -3x + x2 = 1 The x term is -3x. Take half its coefficient (-1.5). Square it (2.25) and add it to both sides. Add '2.25' to each side of the equation. -3x + 2.25 + x2 = 1 + 2.25 Reorder the terms: 2.25 + -3x + x2 = 1 + 2.25 Combine like terms: 1 + 2.25 = 3.25 2.25 + -3x + x2 = 3.25 Factor a perfect square on the left side: (x + -1.5)(x + -1.5) = 3.25 Calculate the square root of the right side: 1.802775638 Break this problem into two subproblems by setting (x + -1.5) equal to 1.802775638 and -1.802775638.Subproblem 1
x + -1.5 = 1.802775638 Simplifying x + -1.5 = 1.802775638 Reorder the terms: -1.5 + x = 1.802775638 Solving -1.5 + x = 1.802775638 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1.5' to each side of the equation. -1.5 + 1.5 + x = 1.802775638 + 1.5 Combine like terms: -1.5 + 1.5 = 0.0 0.0 + x = 1.802775638 + 1.5 x = 1.802775638 + 1.5 Combine like terms: 1.802775638 + 1.5 = 3.302775638 x = 3.302775638 Simplifying x = 3.302775638Subproblem 2
x + -1.5 = -1.802775638 Simplifying x + -1.5 = -1.802775638 Reorder the terms: -1.5 + x = -1.802775638 Solving -1.5 + x = -1.802775638 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1.5' to each side of the equation. -1.5 + 1.5 + x = -1.802775638 + 1.5 Combine like terms: -1.5 + 1.5 = 0.0 0.0 + x = -1.802775638 + 1.5 x = -1.802775638 + 1.5 Combine like terms: -1.802775638 + 1.5 = -0.302775638 x = -0.302775638 Simplifying x = -0.302775638Solution
The solution to the problem is based on the solutions from the subproblems. x = {3.302775638, -0.302775638}Solution
x = {3.302775638, -0.302775638}
| 4y-8x=32 | | 9*3-4+27/9-2= | | 2(x+7)=6(-8) | | 28x=16 | | 62-7x=2x+20 | | 3x^2=2(x+2) | | -(-9y+3)-5=-5-y | | 41-6x=23 | | f(x)=4x-10 | | 2(0)=-2(0) | | x^2=27i | | 5x+6=66 | | 6y+20=-5+4y | | 2(x)=-2x | | 0.5x=2000 | | 66x-4x^2-272=0 | | 5x+6x+7x=180 | | f(x)=-7x+5 | | f(x)=-2x | | 5x+1=123 | | 4x^5-324x=0 | | f(x)=5x^2-12 | | 5a^3(25b-a)/a-25b | | 6w=7w-5 | | 4x+6=2x+6 | | 25b-a/a-25b | | 4x^2+58x-272=0 | | 1z=50 | | 3y=50 | | -4(11-9x)-8=-4(1-5x) | | 6x-(3x-1)=17 | | 2(-x-1)+1=-3(3x-2) |